A new HLA‐A*01 allele – A*01:139. Issue 2 (28th November 2013) - Street, J.; Johnson, J.; Pepperall, J.; Darke, C.
<x xml:space="preserve">Abstract</x> HLA‐A*01:139 differs from A*01:01:01:01 by one nucleotide (383G>C) resulting in an amino acid change of glycine104alanine.